HRV-based thresholds in rowing: Validity and reliability assessment - Held, S.; Rappelt, L.; Wiedenmann, T.; Rommelmann, J.; Gronwald, T.; Donath, L. (European Journal of Sport Science, 2025)
The concurrent validity of lactate thresholds (LT1, LT2) and between-day reliability data from the rowing-specific heart rate variability (HRV)-based thresholds (HRVT) were examined. Thus, 21 rowers (19.6 ± 2.8 years; 1.78 ± 0.09 m; 72.8 ± 11.3 kg) performed two rowing ergometer step tests (starting 100-150 W; 40-50 W increment/4 min) one week apart. Thirteen participants completed both sessions and were included in the reliability analysis. Reliability of power at first (HRVT1) and second HRVT (HRVT2) revealed low standard error of measurements (SEM: HRVT1 = 12 W; HRVT2 = 6 W), coefficient of variation (CV: HRVT1 = 11.5%; HRVT2 = 5.9%), and good to excellent intraclass coefficient (ICC: HRVT1 = 0.83; HRVT2 = 0.93). HRVT2 revealed a sufficient level of agreement (LoA = 35 W) and practicable low minimal detectable changes (MDC = 16 W). In contrast, LoA (46 W) and MDC (32 W) were notably higher for HRVT1. Furthermore, concurrent validity data showed good to excellent ICC values (0.90), low SEM (7 W) and sufficient LoA (35 W) between HRVT2 and power at LT2. Despite good ICC values (0.78), the SEM (LT1 = 12 W) and LoA (41 W) data were notably higher during HRVT1 versus power at LT1 comparison. Thus, HRVT might be a promising, valid, and reliable option to estimate LT in rowing, with HRVT2 having particularly favorable properties as a surrogate for LT2.